LES DÉTERMINANTS DE L’ADOPTION DES NORMES IFRS PAR LES SOCIÉTÉS COTÉES À LA BOURSE DE CASABLANCA - EL HAMZA , M’hammed (Revue du contrôle, de la comptabilité et de l’audit, 2020)
This paper examines factors that could explain the IFRS adoption by Moroccan groups, listed in the Casablanca Market (40 groups). Factors like the size of the group (Positive Accounting Theory), the nationality of the main shareholders, the audit firm (Local / International), the level of debts in the group liabilities (leverage), the group profitability and the market of the company’s main products (Local / Export) could explain the decision of IFRS Adoption by Moroccan Groups. However, other factors relating to the institutional pressers (mainly the World Bank and international financing institution), the development of the accounting profession in Morocco, taxation, and inflation could have a direct impact on groups decision.